MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKATKAN KINERJA GURU PADA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 2 SINABANG KABUPATEN SIMEULUE - Taswir Taswir (Jurnal Ilmiah Didaktika, 2014)
School head master managerial is one things must be conducted systematically and continuously in order to improve the competence and the skill in carrying out the duty to reach the national education goal. The purpose of this study is to describe the school head master managerial at state vocational school SMK 2 Sinabang. This study uses descriptive qualitative approach, and the data collection techniques were observations, interviews, and documentations. The subjects of the research were: school head master, school administration chairman, and the deputy of the school head master. The results shows (1) the school head master’s ability in developing planning programs is formulated by school head master which was started at new school year academic such as supervising, assessing the teacher’s performance, involving the teachers on the trainings, giving extra tasks for some teachers such as vice school headmaster, department chairman, lab chairman, supervisors, and librarian, teachers for training, distribution of additional duties for teachers as a representative example principal, head of department, head of the laboratory, supervisor, and manager of the library; (2) the strategies undertaken by the school head master in teacher performance implementation were: guiding teachers in arranging lesson plan, applying teaching model variation, giving motivation, engaging teachers in some training activities and refreshment courses, and giving the opportunities to the teachers to pursue their study, activating MGMPs activity and KKG forum at school; (3) The impact of the coaching process being carried out by the school head master to improve the teacher performance, will be seen from the teacher changing attitude to be better, namely, the ability of the teacher in setting the plan, implement, and evaluate the teaching–learning process; (4) the constraints being faced in improving the professional capability of teachers among others are: funding problem, timing, and the limitation of the human resources as an instructor/ trainer in the field of vocational, as well as limited training/refresher courses held in conjunction to the professional upgrading of teachers.